PERSEPSI SISWA TENTANG TINDAKAN TEGAS MENDIDIK YANG DIBERIKAN GURU BIMBINGAN DAN KONSELING KEPADA SISWA YANG MELANGGAR PERATURAN SEKOLAH DI SMP N 24 PADANG - Nandiya, Vipi . (Universitas Negeri Padang, 2013)
Abstrak: This research aims to reveal how student’s perception about strict action of education which is given by guidance dan counseling’s teacher at SMP N 24 Padang. This research is descriptive research which is the data was collected by using questionnaires and the subject was the 59 students on the second and the third grade of SMP 24 Padang who violate the rules of school. The finding of this research reveal that studens’ perpection about stict action of education which given by guidance and counseling’s teacher is excellent. Keyword: Strict action of education